Innovative Methods to Learning Kitab Kuning at Elementary School - Muhlas, Abdulloh; Thohari, Imam; Adawiyah, Siti Rabiatul; Salsabila, Shofia; Nurhidayati, Titin (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2024)
Islamic education, with its predominantly Arabic literature, presents a challenge for educators to effectively guide their students in understanding Islam through its primary literature. Curriculum development, learning models, strategies, time allocation, and educators’ abilities are among the agendas that demand innovation and enhanced abilities. At SD Unggulan Assunniyyah Kencong Jember, there is an innovation in Kitab Kuning learning that aims to improve students’ understanding of Islam. We implement this program for students who have completed the final exam of the Qur’an by grouping the Tahfidz class and the Kitab Kuning class. This study employs a qualitative approach of a descriptive nature. Field observation is used to collect data. This study found that implementing a learning model that stimulates students’ understanding can reduce the time it takes to learn the Kitab Kuning. The learning models used are the probing-prompting learning model and the expository learning model, which emphasizes active interaction and practical understanding. We also teach students how to read the Kitab Kuning in the context of Indonesian and pesantren traditions, including the reading of nadzom. The results of this study demonstrate learning innovations that accelerate students’ understanding of Arabic grammar, allowing them to master the Kitab Kuning more efficiently.